Polypyrrole/Metal Oxides-Based Composites/Nanocomposites for Corrosion Protection - Jadhav, Niteen; Kasisomayajula, Subramanyam; Gelling, Victoria Johnston (Frontiers in Materials, 2020)
Corrosion is of paramount interest of researchers all around the world owning to its disastrous impact on economy and safety. New strategies based on novel materials have been employed to mitigate corrosion. Conducting polymer-based nanocomposites is a class of materials which has shown promise for corrosion protection. This paper will focus on the specific case of the Conducting polymer-based nanocomposites for corrosion protection and one important case will be discussed in detail. Corrosion protection offered by Polypyrrole (PPy)/Fe2O3 based composite coating for cold rolled substrate is characterized in this paper by Electrochemical Impedance Spectroscopy (EIS) and Open Circuit Potential (OCP) measurements. It was found that PPy/Fe2O3 based composite coating provides better corrosion performance after 40 days exposure to ASTM B117 salt fog test conditions. This improved performance was attributed to the increased surface area of PPy and passivating nature of composite resulting from the redox activity provided by PPy.